Somatic cytogenotoxicity of first-line anti-tuberculosis drugs using the mouse micronucleus assay - Adekunle A. Bakare; Charles T. Beckley; Obi M. Ebelechukwu; Adeyinka M. Gbadebo; Motunrayo M. Coker; Omonike C. Bakare; Olukunle S. Fagbenro; Okunola A. Alabi (Academia Biology)
Rifampicin, isoniazid, ethambutol, pyrazinamide, and/or their fixed-dose combination (FDC) are the first-line tuberculosis (TB) antibiotics used as a 6-month regimen. We evaluated the cytogenotoxic effects of these drugs using the murine micronucleus assay. Male Swiss albino mice were intraperitoneally exposed for 5 consecutive days to 1.25, 2.50, 5.00, 10.00, and 20.00 mg/kg bw of rifampicin; 0.63, 1.25, 2.50, 5.00, and 10.00 mg/kg bw of isoniazid; 1.88, 3.75, 7.50, 15.00, and 30.00 mg/kg bw of ethambutol; 3.13, 6.25, 12.50, 25.00, and 50.00 mg/kg bw of pyrazinamide; and 3.50, 7.00, 14.00, 28.00, and 56.00 mg/kg bw of FDC. Normal saline and cyclophosphamide (20 mg/kg bw) were used as negative and positive controls, respectively. At the tested doses, the drugs induced a dose-independent increase in micronucleated polychromatic erythrocyte (MNPCE) and micronucleated normochromatic erythrocyte (MNNCE) compared with the negative control. The induction was statistically significant at most of the tested doses of the drugs. There was a significant increase in the percentage PCE:NCE ratio in the bone marrow cells of mice at the tested doses of isoniazid, pyrazinamide, and the FDC. These results indicate that the individual anti-TB drug and their FDC possess DNA-damaging potential in the somatic cells of mice.